PENGARUH E-BANKING, KUALITAS PELAYANAN DAN KUALITAS KOMUNIKASI TERHADAP LOYALITAS NASABAH (STUDI KASUS NASABAH BANK BCA KOTA SEMARANG) - Yuliani, Kwik Cynthia; Luhgiatno, Luhgiatno (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2022)
Banking companies have the main weapon to keep their customers loyal. Loyal customers will increase company profits. This research was conducted with the aim of knowing and analyzing the joint effect of e-banking, service quality and communication quality on customer loyalty at Bank BCA Semarang City. The research was conducted using a quantitative approach. The research sample was 100 BCA Semarang customers, with the research instrument using a questionnaire. The analysis technique uses multiple linear regression. The results showed that 1), e-banking proved to have a positive and significant effect on customer loyalty, 2) service quality proved to have a positive and significant effect on customer loyalty, 3) communication quality proved to have a positive and significant effect on customer loyalty, and 4) e-banking banking, service quality and communication quality proved to have a positive and significant effect on customer loyalty of BCA Semarang City.Keywords: e-banking, service quality, communication quality, loyalty.